Toxic masculinity and mental condition of young men in Poland aged 18-30 - Katarzyna Janiak; Krzysztof Zdziarski (Kazimierz Wielki University, 2022)
The article presents conformity to toxic masculinity in the perspective of mental condition of young men in Poland aged 18-30. The first part introduced the concept of toxic masculinity and its implications on men's mental condition and general social functioning. The conformity to toxic masculinity has been investigated by using self-constructed questionnaire and mental condition has been tested by using DASS-21 questionnaire. The study has been conducted on group of 127 men living in Poland and the data was collected by using online methods. Research results shows very little, statistically insignificant relationship between conformity to toxic masculinity and mental condition of young men, however some differences have been observed in terms of place of living and sexual orientation when it comes to level of conformity to toic masculinity and level of mental condition.